ผลสัมฤทธิ์ของการเรียนภาษาอังกฤษด้วยตนเอง โดยใช้โปรแกรม Edusoft’s English Discovery ENGLISH ACHIEVEMENT OF SELF-DIRECTED LEARNING THROUGH EDUSOFT’S ENGLISH DISCOVERIES - ศรีโนนยาง, ประดิษฐ์; ทาวงศ์ษา, กิตติพัฒน์; อภัยโส, พลภัทร; โชติชัย, บรรจบ (วารสารศรีล้านช้างปริทรรศน์, 2018)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาผลสัมฤทธิ์ของการเรียนภาษาอังกฤษด้วยตนเอง โดยใช้โปรแกรม Edusoft’s English Discoveries (2) เปรียบเทียบความสามารถด้านภาษาอังกฤษของนักศึกษาก่อนและหลังการเรียนรู้โดยใช้โปรแกรม Edusoft’s English Discoveries และ (3) ศึกษาความพึงพอใจต่อการจัดการเรียนรู้ภาษาอังกฤษด้วยตนเองของนักศึกษาโดยใช้โปรแกรม Edusoft’s English Discoveries กลุ่มเป้าหมายที่ใช้ในการศึกษาเป็นนักศึกษาคณะศึกษาศาสตร์ สาขาวิชาการสอนภาษาอังกฤษ มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตศรีล้านช้าง ที่เรียนรู้ภาษาอังกฤษด้วยตนเองโดยใช้โปรแกรม Edusoft’s English Discoveries จนผ่านระดับ Basic 1 – 3 จำนวน 68 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบวัดผลสัมฤทธิ์ของการเรียนรู้ภาษาอังกฤษด้วยตนเอง ประกอบด้วยแบบทดสอบก่อนเรียน (pretest) และแบบทดสอบหลังเรียน (posttest) ซึ่งพัฒนาจากแบบทดสอบ Exit Test – Basic 1 – 3 ที่มาพร้อมกับโปรแกรม ผลการเรียนรู้ภาษาอังกฤษส่วน Student Score ที่บันทึกอยู่ในโปรแกรม และแบบสอบถามความพึงพอใจของผู้เรียนที่เป็นแบบมาตราส่วนประมาณค่า 5 ระดับของลิเคอร์ท สถิติที่ใช้ในการวิจัยประกอบด้วยค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าทีแบบไม่เป็นอิสระจากกัน ผลการวิจัยพบว่า 1) การเรียนรู้ภาษาอังกฤษด้วยตนเองโดยใช้โปรแกรม Edusoft’s English Discoveries สามารถช่วยทำให้ผลสัมฤทธิ์ของการเรียนรู้ภาษาอังกฤษด้วยตนเองของนักศึกษาสูงขึ้น โดยนักศึกษาส่วนใหญ่ผ่านเกณฑ์ 55 คะแนน และมีผลการเรียนสูงกว่าร้อยละ 60 หรือตั้งแต่ระดับเกรด C ขึ้นไป 2) ผลการทดสอบหลังการเรียนรู้ภาษาอังกฤษด้วยตนเองของนักศึกษาโดยใช้โปรแกรม Edusoft’s English Discoveries สูงกว่าผลการทดสอบก่อนการเรียนรู้อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) นักศึกษามีความพึงพอใจต่อการจัดการเรียนรู้ภาษาอังกฤษด้วยตนเองโดยใช้โปรแกรม Edusoft’s English Discoveries โดยรวมอยู่ในระดับมาก (x̄ = 3.74) เนื่องจากโปรแกรมมีการออกแบบเนื้อหาบทเรียนอย่างต่อเนื่อง มีความยากง่ายเหมาะสมกับระดับของผู้เรียน มีการเชื่อมโยงความรู้เดิมกับความรู้ใหม่ ช่วยให้เรียนรู้ได้ด้วยตนเองสะดวกยิ่งขึ้น นอกจากนี้บทเรียนยังมีความยืดหยุ่น สนองความแตกต่างระหว่างบุคคล และผู้เรียนสามารถควบคุมลำดับเนื้อหา ลำดับการเรียนได้เอง เนื้อหาบทเรียนและแบบทดสอบกระตุ้นให้ผู้เรียนต้องการเรียนรู้ด้วยตนเอง แบบทดสอบสอดคล้องกับเนื้อหาและตรงประเด็นกับเนื้อหาที่จะศึกษา             The objectives of the research article were (1) to study Mahamakut Buddhist Univertisy, Srilanchang Campus students’ English achievement of self-directed learning through Edusoft’s English Discoveries, (2) to compare the students’ English competency before and after self-directed learning throught Edusoft’s English Discoveries, and (3) to study the students’ satisfaction with English self-directed learning through Edusoft’s English Discoveries. The target group of the research were 58 English teaching students of MBUSLC’s Faculty of Education, learning English by themselves through Edusoft’s English Discoveries and passing the Basic 1 – 3 levels. The instuments of the research were the pretest and the posttest for English achievement of self-directed learning through Edusoft’s English Discoveries, which were developed from the program’s Exit Test – Basic 1 – 3, English learning results of the students recorded in the program’s Student Scores report, and the Likert’s five-point rating scale questionnaire on the students’ satisfaction with English self-directed learning through Edusoft’s English Discoveries. The statistics used for data analysis were comprised of percentage, arithmetic mean, standard deviation and t-test for dependent samples.             The results of the research were found as follows: English self-directed learning through Edusoft’s English Discoveries was found to improve the students’ English achievement of self-directed learning, and the majority of the students were found to pass the minimal criteria of 55 scores and to have higher than 60% (or higher than Grade C) of learning results. The posttest for the stendents’ English achievement of self-directed learning through Edusoft’s English Discoveries was found higher than the pretest at a statistically significant level of .05. The students’ satisfaction with English self-directed learning through Edusoft’s English Discoveries was found to be overall at a high level (x̄ = 3.74) because the program’s content was well designed for continuous learning, the content difficulty was designed suitable for the learner’s level, and the learner’s old knowledge was linked to new knowledge for the sake of self-directed learning. In addition, the program’s content was designed flexible and responded to individual differences. The order of content and learning was easily controlled by the learner himself. The content and tests were found to encourage the learner’s requirement to learn by himself, and the tests were found resorted to and in accordance with the content to be learnt.